Patterns of genetic diversity of the cryptogenic red alga Polysiphonia morrowii (Ceramiales, Rhodophyta) suggest multiple origins of the Atlantic populations. Issue 16 (19th July 2016) - Geoffroy, Alexandre; Destombe, Christophe; Kim, Byeongseok; Mauger, Stéphane; Raffo, María Paula; Kim, Myung Sook; Le Gall, Line
Abstract: The red alga Polysiphonia morrowii, native to the North Pacific (Northeast Asia), has recently been reported worldwide. To determine the origin of the French and Argentine populations of this introduced species, we compared samples from these two areas with samples collected in Korea and at Hakodate, Japan, the type locality of the species. Combined analyses of chloroplastic ( rbc L) and mitochondrial ( cox 1) DNA revealed that the French and Argentine populations are closely related and differ substantially from the Korean and Japanese populations. The genetic structure of P. morrowii populations from South Atlantic and North Atlantic, which showed high haplotype diversity compared with populations from the North Pacific, suggested the occurrence of multiple introduction events from areas outside of the so‐called native regions. Although similar, the French and Argentine populations are not genetically identical. Thus, the genetic structure of these two introduced areas may have been modified by cryptic and recurrent introduction events directly from Asia or from other introduced areas that act as introduction relays. In addition, the large number of private cytoplasmic types identified in the two introduced regions strongly suggests that local populations of P. morrowii existed before the recent detection of these invasions. Our results suggest that the most likely scenario is that the source population(s) of the French and Argentine populations was not located only in the North Pacific and/or that P. morrowii is a cryptogenic species. Abstract : The red alga Polysiphonia morrowii has been reported worldwide and we determine (with combined analyses of chloroplastic and mitochondrial DNA) the origin of the French and Argentine introduced populations. The genetic structure of P. morrowii populations from introduced areas, which displayed high haplotype diversity compared with populations from native area, suggested the occurrence of multiple introduction events. Our study suggests recent recurrent introduction events through human activities and we therefore conclude that P. morrowii is a cryptogenic species.